2019
DOI: 10.1093/neuros/nyz070
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 90-Day and 1-Year Mortality in Spinal Metastatic Disease: Development and Internal Validation

Abstract: BACKGROUND Increasing prevalence of metastatic disease has been accompanied by increasing rates of surgical intervention. Current tools have poor to fair predictive performance for intermediate (90-d) and long-term (1-yr) mortality. OBJECTIVE To develop predictive algorithms for spinal metastatic disease at these time points and to provide patient-specific explanations of the predictions generated by these algorithms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
152
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(155 citation statements)
references
References 35 publications
3
152
0
Order By: Relevance
“…In their study, the nomogram was found intuitive and demonstrated a comparable level of performance. Then, in 2019, the SORG used machine-learning algorithms to develop a novel prognostic model for metastatic spinal disease [28], which was externally validated in subsequent studies [29,30].…”
Section: Classification-based Decision-making Systemsmentioning
confidence: 99%
“…In their study, the nomogram was found intuitive and demonstrated a comparable level of performance. Then, in 2019, the SORG used machine-learning algorithms to develop a novel prognostic model for metastatic spinal disease [28], which was externally validated in subsequent studies [29,30].…”
Section: Classification-based Decision-making Systemsmentioning
confidence: 99%
“…The usefulness of PLR has been demonstrated for predicting survival within 6 and 12 months, treatment failure, and readmissions in patients with spinal metastasis [25] . Also, in the study conducted by Karhade et al [24] , a poor prognosis indicated by TLC seems to be related to postoperative complications (i.e., short-term outcomes), while a poor prognosis indicated by other inflammatory biomarkers seems to be related to tumor progression (i.e., medium-and long-term outcomes).…”
Section: Discussionmentioning
confidence: 95%
“…Neural network techniques have also been applied to develop predictive algorithms for postoperative complications following anterior cervical discectomy and fusion [ 56 ], and to evaluate clinically relevant improvement in leg pain, back pain and functional disability after lumbar disc herniation (LDH) surgery [ 59 ], and to automatically quantify muscle fat infiltration following whiplash injury [ 62 ]. In addition, ANNs have been shown to accurately predict survival, discharge and hospital readmission rates following spinal metastasis surgery [ 57 , 60 , 61 ], to predict discharge to rehabilitation and unplanned readmissions in patients receiving spinal fusion [ 63 ], and to predict prolonged opioid prescription after surgery for LDH [ 64 ]. Last but not least, ANNs have been used to predict the survival rate following a spinopelvic chondrosarcoma diagnosis [ 65 ] and to predict the occurrence of four types of major complications, namely cardiac complications, wound complications, venous thromboembolism, and mortality in the patients undergoing spine fusion, and it has achieved better results than the commonly used clinical scoring methods [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioned that preoperative prediction of opioid use could improve the risk stratification, shared decision-making, and patient counseling before LDH surgery [ 84 ]. In addition, Karhade et al [ 61 ] developed a machine learning tool to automatically predict 90-day and 1-year mortality in spinal metastatic disease ( https://sorg-apps.shinyapps.io/spinemetssurvival/ ) [ 85 ]. Meanwhile, the same group also developed a machine learning algorithm for predicting discharge disposition after elective inpatient surgery for lumbar disc disease [ 55 ], the model is available at https://sorg-apps.shinyapps.io/discdisposition/ [ 86 ].…”
Section: Discussionmentioning
confidence: 99%